Electrodynamic properties of matrix dispersed systems with two-layer inclusions - Grechko, L.G.; Mal’nev, V.N.; Shkodа, N.G.; Shostak, S.V. (Поверхность, 2002)
Theoretical approach for calculation of the effective dielectric permittivity (ē) of matrix dispersed systems (MDS) that consist of a dielectric matrix with randomly arranged two-layer spherical inclusions of different radiuses has been proposed and departures from the Maxwell-Garnet formula due to increasing of an inclusion volume fraction are studied. It is shown that the effects of direct dipole-dipole interactions between inclusions become important in this case. In the electrostatic approximation we have exactly solved the problem of a response of this N–particle system on the external electric field and obtained corrections to the Maxwell-Garnet formula for ē with account of the pair dipole-dipole interaction between inclusions.